2018
DOI: 10.1177/0333102418759786
|View full text |Cite
|
Sign up to set email alerts
|

ARISE: A Phase 3 randomized trial of erenumab for episodic migraine

Abstract: Background Calcitonin gene-related peptide plays an important role in migraine pathophysiology. Erenumab, a human monoclonal antibody that inhibits the calcitonin gene-related peptide receptor, is being evaluated for migraine prevention. Methods In this randomized, double-blind, placebo-controlled, phase 3 study, 577 adults with episodic migraine were randomized to placebo or 70 mg erenumab; 570 patients were included in efficacy analyses. Primary endpoint was change in monthly migraine days. Secondary endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
522
4
29

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 478 publications
(583 citation statements)
references
References 34 publications
28
522
4
29
Order By: Relevance
“…In previous global studies in episodic migraine, 7,9,10 erenumab 70 mg led to statistically significant improvements in multiple outcome measures, whereas improvements with 21 and 7 mg monthly doses were not statistically significant. In previous global studies in episodic migraine, 7,9,10 erenumab 70 mg led to statistically significant improvements in multiple outcome measures, whereas improvements with 21 and 7 mg monthly doses were not statistically significant.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…In previous global studies in episodic migraine, 7,9,10 erenumab 70 mg led to statistically significant improvements in multiple outcome measures, whereas improvements with 21 and 7 mg monthly doses were not statistically significant. In previous global studies in episodic migraine, 7,9,10 erenumab 70 mg led to statistically significant improvements in multiple outcome measures, whereas improvements with 21 and 7 mg monthly doses were not statistically significant.…”
Section: Methodsmentioning
confidence: 67%
“…[7][8][9][10] Erenumab has also demonstrated efficacy in the prevention of chronic migraine, 11 including patients who had failed previous preventive migraine treatments. To date, 3 global, randomized, double-blind, placebo-controlled, clinical studies have demonstrated the efficacy of erenumab in the prevention of episodic migraine, including patients who had failed previous preventive migraine treatments.…”
Section: Introductionmentioning
confidence: 99%
“…65 Patients who received erenumab had a −2.9 days change in monthly migraine days (MMD), vs −1.8 days for placebo. 65 Patients who received erenumab had a −2.9 days change in monthly migraine days (MMD), vs −1.8 days for placebo.…”
Section: Cgrp Monoclonal Antibodiesmentioning
confidence: 99%
“…In the phase 3 STRIVE trial, patients with episodic migraine received monthly doses of either 70, 140 mg, or placebo for 6 months. 65,66 There is evidence supporting the use of erenumab as preventive treatment in patients with refractory migraine. There was 50% or greater reduction in mean number of migraine days per month in 43.3% of patients in the 70 mg group and in 50.0% of patients in the 140 mg group (26.6% for placebo).…”
Section: Cgrp Monoclonal Antibodiesmentioning
confidence: 99%
“…Existing preventive treatments are not effective for everyone, and some are poorly tolerated. Although trials of CGRP mAbs reported a modest reduction in days with migraine per month compared with placebo, the treatments had few adverse effects 2345…”
mentioning
confidence: 99%